Minimal and Maximal Solutions of Second-order Functional Difference Equations - S. Sindhuja, J. Daphy Louis Lovenia, A. P. Lavanya, G. Gomathi Jawahar, D. Darling Jemima (International Journal of Advanced Science and Technology, 2020)
Minimal and Maximal Solutions of Second-order Functional Difference Equations